FORMATION STAGES OF THE DIWAN SYSTEM OF THE ARAB CALIPHATE - Ziyodilla Zinatullayev Izzatilla o‘g‘li (Bright Mind Publishing, 2025)
The article examines the emergence of the first Islamic state in the Arabian Peninsula, the period of the Rashidun caliphate and the formation of the ruling system of the Arab Caliphate on the basis of primary sources and scientific literature.
Keywords: Mecca, Yathrib, Medina, city-state, caliph, caliphate administration.